Chitosan surface modification modulates the mucoadhesive, permeation and anti-angiogenic properties of gellan gum/bevacizumab nanoparticles - Carvalho, Suzana Gonçalves [UNESP]; Haddad, Felipe Falcão [UNESP]; dos Santos, Aline Martins [UNESP]; Scarim, Cauê Benito [UNESP]; Ferreira, Leonardo Miziara Barboza [UNESP]; Meneguin, Andréia Bagliotti [UNESP]; Chorilli, Marlus [UNESP]; Gremião, Maria Palmira Daflon [UNESP] (My University, 2024)
Bevacizumab (BVZ) was the first monoclonal antibody approved by the FDA and has shown an essential advance in the antitumor therapy of colorectal cancer (CRC), however, the systemic action of BVZ administered intravenously can trigger several adverse effects. The working hypothesis of the study was to promote the modulation of the mucoadhesion properties and permeability of the BVZ through the formation of nanoparticles (NPs) with gellan gum (GG) with subsequent surface modification with chitosan (CS). NPs comprising BVZ and GG were synthesized through polyelectrolyte complexation, yielding spherical nanosized particles with an average diameter of 264.0 ± 2.75 nm and 314.0 ± 0.01 nm, polydispersity index of 0.182 ± 0.01 e 0.288 ± 0.01, and encapsulation efficiency of 29.36 ± 0.67 e 60.35 ± 0.27 mV, for NPs without (NP_BVZ) and with surface modification (NP_BVZ + CS). The results showed a good ability of nanoparticles with surface modification to modulate the NPs biological properties.
Keywords: Angiogenesis; Antibody; Bevacizumab; Chitosan; Gellan gum; Polymeric nanoparticle